Thrombin contributes to protective immunity in pneumonia‐derived sepsis via fibrin polymerization and platelet–neutrophil interactions - Claushuis, T. A. M.; Stoppelaar, S. F.; Stroo, I.; Roelofs, J. J. T. H.; Ottenhoff, R.; Poll, T.; Veer, C. (Journal of thrombosis and haemostasis, 2017)
Essentials Immunity and coagulation are linked during sepsis but the role of thrombin is not fully elucidated. We investigated the effect of thrombin inhibition on murine Klebsiella pneumosepsis outcome. Thrombin is crucial for survival and limiting bacterial growth in pneumonia derived sepsis. Thrombin improves host defense via fibrin and enhancement of platelet‐neutrophil interactions. Summary Background Innate immunity and coagulation are closely linked during sepsis. Their interaction can be detrimental to the outcome because of microvascular failure but can also enhance host defense. The role of thrombin therein has not been fully elucidated. Objective We aimed to investigate the contribution of thrombin to the host response during pneumonia‐derived sepsis. Methods Mice treated with the specific thrombin inhibitor dabigatran or control chow were infected with the common human sepsis pathogen Klebsiella (K.) pneumoniae via the airways. In subsequent infection experiments, mice were additionally treated with ancrod to deplete fibrinogen. Ex vivo Klebsiella growth was assessed by incubating human whole blood or specific blood components in various conditions with Klebsiella. Results Thrombin inhibition by dabigatran enhanced bacterial outgrowth and spreading, and accelerated mortality. Thrombin inhibition did not influence neutrophil recruitment to the lung or activation or neutrophil extracellular trap formation. Dabigatran reduced D‐dimer formation and fibrin deposition in the lung. Fibrin depletion also enhanced bacterial outgrowth and spreading, and thrombin inhibition had no additional effect. Both thrombin and fibrin polymerization inhibited ex vivo Klebsiella outgrowth in human whole blood, which was neutrophil dependent, and the effect of thrombin required the presence of platelets and platelet protease activated receptor‐1. In vivo thrombin inhibition reduced platelet–neutrophil complex formation and endothelial cell activation, but did not prevent sepsis‐induced thrombocytopenia or organ damage. Conclusions These results suggest that thrombin plays an important role in protective immunity during pneumonia‐derived sepsis by fibrin polymerization and enhancement of platelet–neutrophil interactions.